Lessons From the Open Library of Humanities - Eve, Martin Paul; Vega, Paula Clemente; Edwards, Caroline (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2020)
The Open Library of Humanities was launched almost half a decade ago with funding from the Andrew W. Mellon Foundation. In this article, we outline the problems we set out to address and the lessons we learned. Specifically, we note that, as we hypothesized, academic libraries are not necessarily classical economic actors; that implementing consortial funding models requires much marketing labour; that there are substantial governance and administrative overheads in our model; that there are complex tax and VAT considerations for consortial arrangements; and that diverse revenue sources remain critical to our success.